2017
DOI: 10.1111/hepr.12933
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized, controlled study of the efficacy of transcatheter arterial chemoembolization with miriplatin for hepatocellular carcinoma

Abstract: Miriplatin proved more effective than epirubicin in TACE for unresectable HCC. The trial described in this work has been registered under the trial number: UMIN000004790.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…37 They reported that the combination therapy of miriplatin and cisplatin had significantly better progression-free survival and overall DCR. Recently, as miriplatin has become the standard drug in addition to anthracyclines in TACE in Japan, [38][39][40] the results of the present study also provide useful basic information whether to add TAI using cisplatin to TACE using miriplatin in the future.…”
Section: Discussionmentioning
confidence: 64%
“…37 They reported that the combination therapy of miriplatin and cisplatin had significantly better progression-free survival and overall DCR. Recently, as miriplatin has become the standard drug in addition to anthracyclines in TACE in Japan, [38][39][40] the results of the present study also provide useful basic information whether to add TAI using cisplatin to TACE using miriplatin in the future.…”
Section: Discussionmentioning
confidence: 64%
“…Transcatheter arterial therapy, including TACE and TAI using lipiodol and anticancer agents, is widely used to treat HCC (17). In TACE, we administer anticancer agents and embolize the tumor nutrient arteries using gelatin sponge particles.…”
Section: Discussionmentioning
confidence: 99%
“…In October 2009, miriplatin, belonging to the family of platinum agents, was approved as a TACE agent for treating HCC. The results of several previous studies on TACE using miriplatin suggest that miriplatin may be one of the safest and most efficacious therapeutic agents (1,6,17). However, TACE is not recommended in patients with distant metastases and vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, a total of 12 retrospective and prospective reports have been published regarding miriplatin compared with other anticancer drugs in the treatment of TACE (Table ). Although miriplatin seemed to have an ideal chemical and pharmacological structure in lipiodol‐using TACE, Miyayama et al reported that the anticancer activity was not higher than conventional TACE using ordinary epirubicin.…”
Section: Transcatheter Arterial Therapymentioning
confidence: 99%
“…As the viscosity of miriplatin–lipiodol suspension is higher than lipiodol alone, it hardly flows into the peripheral hepatic artery compared with other emulsified anticancer drugs. We should realize the efficiency of the use of warmed miriplatin suspension at transcatheter arterial injection: two retrospective comparisons showed the objective response rates of warmed miriplatin were higher and one prospective study showed a longer time to tumor progression . Miriplatin is currently used for non‐selective infusion for bilobar multiple HCCs, epirubicin‐refractory HCC, and for targeted balloon‐occluded TACE (B‐TACE) against localized HCCs, but ideal use of warming and ways of injection are not fully elucidated.…”
Section: Transcatheter Arterial Therapymentioning
confidence: 99%